Insecticidal Efficiency of Intergeneric Recombinants between Bacillus thuringiensis and Bacillus subtilis Against Viability of Cotton Leafworm - Saad A. Alotaibi, (Journal of Basic & Applied Sciences, 2012)
Bacillus thuringiensis is the most widely applied biological insecticide and is used to manage insects that affect forestry and agriculture. This ubiquitous spore-forming bacterium kills insect larvae largely through the action of insecticidal crystal proteins and is commonly deployed as a direct bacterial spray. Moreover, this study aimed to measuring recombinant efficiency of recombinant bioinsecticides (Bacillus thuringiensis x Bacillus subtilis) against Spodoptera litoralis. For decades, the mechanism of insect killing has been assumed to be toxin-mediated lysis of the gut epithelial cells, which leads to starvation, or B. thuringiensis septicemia. In the present work, two strains of Bacillusstrains belonging to two serotypes and four of their transconjugants were screened with respect to their insecticidal activity against lepidopterous cotton pest. Two strains of Bacillus were screened for their drug resistance to be used as a genetic markers to identify bacterial strains in the conjugation process. B. subtilis was found to be resistant to crystal violet and sensitive to hiconcil. Although, B. thuringiensis was found to be sensitive to crystal violet, except for it was resistant to hiconcil. Bacterial transconjugants isolated from conjugation between both strains were more resistant to both crystal violet and hiconcil. Two groups of crystals and spores have been isolated within Bacillus strains and their transconjugants. The results appeared a highly potent recombinant efficiency in reducing leaves consumption at 72h (crystals), 120h (crystals + endospores) and 144h (crystals + endospors). However, transcongugants B and c was more effective in reducing the rate of consumption at all different times of larval ages. The weight of surviving larvae feeding on leaves sprayed with recombinants of Cry, Cry + End. was markedly reduced especially at 48h of larval age. However, ransconjugants A, B and C appeared recombinant efficiency in reduced survival percentage of larvae at 96h, 120h, 144h and 168h in response to recombinants of both cry, cry + endospores. The same trend was also shown by transconjugant C at 48h and 72h in response to both recombinant bioinsecticides. The results indicated that recombinant endotoxin preparations containing crystals + endospores was more effective against Spodoptera litoralisthan that containing crystals.